The Co-Determinant of Capital Structure and Profitability Based on the Supply Chain Strategy: Evidence from Manufacturing Sector in Indonesia - Teddy Chandra; Achmad Tavip Junaedi; Evelyn Wijaya; Stefani Chandra; Priyono Priyono (International Journal of Supply Chain Management, 2019)
This study aims to analyze the simultaneous relationship between supply chain strategy and profitability. This study will also analyze the effect of capital structure and profitability on firm value based on the supply chain strategy. Furthermore, it will analyze the factors that influence capital structure, profitability and firm value in manufacturing companies in Indonesia. The endogenous variables used are profitability, capital structure and firm value, while the exogenous variables used are firm size, growth, tangibility, liquidity, volatility, uniqueness, advertising and financial flexibility. The population of this research is manufacturing companies listed on the Indonesia Stock Exchange. The sampling technique used was the purposive sampling. There were 117 companies that became the research samples. The observation period began in 2010-2016, so the amount of the data used in this study became 819 units of analysis. The analysis technique uses path analysis. The results of the research showed that there was a simultaneous relationship between profitability and capital structure. Profitability and firm size have a significant effect on firm value, while capital structure and growth do not have a significant effect on the firm value. Firm size, growth, tangibility and capital structure affect the profitability, while liquidity, volatility and advertising have no significant effect on profitability. Firm size, uniqueness, financial flexibility and profitability have a significant effect on capital structure, while growth, tangibility, liquidity and volatility have no significant effect on capital structure.